Chorioallantoic membrane (CAM) assay to study treatment effects in diffuse intrinsic pontine glioma - Power, Erica A.; Fernandez-Torres, Jenelys; Zhang, Liang; Yaun, Ruiyi; Lucien, Fabrice; Daniels, David J. (PLOS ONE, 2022)
Diffuse intrinsic pontine glioma (DIPG) is a lethal pediatric brain tumor. While there are a number of in vivo rodent models for evaluating tumor biology and response to therapy, these models require significant time and resources. Here, we established the chick-embryo chorioallantoic (CAM) assay as an affordable and time efficient xenograft model for testing a variety of treatment approaches for DIPG. We found that patient-derived DIPG tumors develop in the CAM and maintain the same genetic and epigenetic characteristics of native DIPG tumors. We monitored tumor response to pharmaco- and radiation therapy by 3-D ultrasound volumetric and vasculature analysis. In this study, we established and validated the CAM model as a potential intermediate xenograft model for DIPG and its use for testing novel treatment approaches that include pharmacotherapy or radiation.